Triple Jeopardy: Complexities of Racism, Sexism, and Ageism on the Experiences of Mental Health Stigma Among Young Canadian Black Women of Caribbean Descent - Taylor, Dalon; Richards, Donna (Frontiers in Sociology, 2019)
This article explores how the intersection of race, gender, and age intertextually complicate and nuance the experience of mental health stigma among young Black women of Caribbean descent living in Canada. The Mental Health Commission of Canada acknowledged that mental health stigma continues to affect the help-seeking behavior of young adults. Some youth-serving agencies and many advocates within Black communities have become increasingly vocal about mental health stigma and the lackluster response to the needs of Black youth (e.g., no increase in funding for the Substance Abuse Program for African, Canadian and Caribbean Youth – SAPACCY, since the program was established in the mid-1990s). The issue of mental health stigma within the African, Caribbean, and Black Canadian (ACB) communities is widely known and often discussed at public forums. Several recent mental health forums and mental health initiatives held in Toronto made it clear that mental health in Black communities is at a crisis point in the Greater Toronto Area (GTA) and possibly across Canada. Forum discussions also revealed that the issue is further compounded by the intersection of race, gender, and age. In addition, while research studies have also identified stigma as a barrier to accessing mental health services and/or supports, there is a paucity of research on how mental health stigma, when complicated by the experience of racism, sexism, and ageism, affects access to services among young Black women of Caribbean descent. This lack of research on Caribbean women’s experience with mental illness limits insights into concepts, issues, and problems that directly impact broader issues related to mental health in Canada.